PENGARUH INTEGRASI KONTEN DIGITAL TERHADAP NIAT SERTIFIKASI HALAL WIRAUSAHAWAN MUSLIM DI ERA INFORMASI DIGITAL: SURVEI PADA WIRUSAHAWAN MUSLIM UMKM KARAWANG - Irfan Mujahidin; Iskandar Sulaeman (Universitas Mathla’ul Anwar Banten, 2025)
Halal certification is an important aspect for Muslim business actors, not only as a fulfillment of religious obligations, but also as a strategy to increase competitiveness. The development of digital technology through the SIHALAL application and BPJPH online services provides convenience for entrepreneurs’ UMKM to access information and apply for certification. However, even though the digital adoption rate of entrepreneurs’ UMKM in Karawang is quite high, the number of businesses that already have halal certificates is still very limited. This study aims to analyze the effect of digital content integration on halal certification intentions Muslim Entrepreneurs in the Digital Information Era in the Food and Beverage Sector. With a quantitative approach, data was collected through a survey of 120 respondents and analyzed using linear regression tests and hypothesis tests. The results showed that the integration of digital content had a positive and significant effect on the intention of halal certification with an R² value of 47.2% with a regression model of Y = 1.215 + 0.732X. These findings support the Theory of Planned Behavior and Technology Acceptance Model, and affirm the role of digitalization in encouraging halal compliance among Muslim Entrepreneurs in UMKM Karawang.